2009
DOI: 10.1371/journal.pone.0005074
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrio cholerae Cytolysin Promotes Chloride Secretion from Intact Human Intestinal Mucosa

Abstract: BackgroundThe pathogenicity of the Vibrio cholerae strains belonging to serogroup O1 and O139 is due to the production of virulence factors such as cholera toxin (CT) and the toxin-coregulated pilus (TCP). The remaining serogroups, which mostly lack CT and TCP, are more frequently isolated from aquatic environmental sources than from clinical samples; nevertheless, these strains have been reported to cause human disease, such as sporadic outbreaks of watery diarrhoea and inflammatory enterocolitis. This eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Examples of PFTs that directly damage epithelial cells are GAS SLO, S. aureus alpha-toxin (190), B. thuringiensis Cry5B (330), C. perfringens ␤-toxin (77) and ε-toxin (81), and V. cholerae VCC (205,206). Findings in vitro for GAS, B. anthracis, and C. perfringens further support the notion that PFTs induce barrier dysfunction (465)(466)(467).…”
Section: Induction Of Barrier Dysfunctionmentioning
confidence: 69%
See 1 more Smart Citation
“…Examples of PFTs that directly damage epithelial cells are GAS SLO, S. aureus alpha-toxin (190), B. thuringiensis Cry5B (330), C. perfringens ␤-toxin (77) and ε-toxin (81), and V. cholerae VCC (205,206). Findings in vitro for GAS, B. anthracis, and C. perfringens further support the notion that PFTs induce barrier dysfunction (465)(466)(467).…”
Section: Induction Of Barrier Dysfunctionmentioning
confidence: 69%
“…Non-O1 and non-O139 serotype V. cholerae strains, which are usually cholera toxin (CT) and toxin-coregulated pilus A (TcpA) negative, can still cause watery diarrhea (205,206). It was found that in such strains VCC induces a CT-like effect on excised human intestine, in that it causes leakage of Cl Ϫ ions, resulting in an outflow of Na ϩ and water (206). Barrier dysfunction in other tissues.…”
Section: Pft-induced Barrier Dysfunctionmentioning
confidence: 99%
“…The hly gene that encodes the VCC protein is widespread across both pathogenic and environmental strains of V. cholerae, suggesting that VCC may impart an advantage to the organism (42). Although the precise role of VCC in V. cholerae infection is unknown, VCC is the primary virulence factor in V. cholerae infection with non-O1, non-O139 strains that do not produce cholera toxin (12,46). The immune response to VCC is not well understood; however, recent studies suggest that VCC may promote a Th2 response in V. cholerae infection (2).…”
Section: We Hypothesize That Protective Immunity Is Mediated By Anamnmentioning
confidence: 99%
“…hemolysin | membrane protein | X-ray crystallography | virulence factor T he devastating human pathogen Vibrio cholerae, which is endemic in many parts of the globe and responsible for thousands of deaths annually, produces a cell-damaging toxin, Vibrio cholerae cytolysin (VCC), that permeabilizes human intestinal and immune cells (1)(2)(3) and significantly facilitates intestinal colonization in mouse models (4). Although VCC's involvement as a virulence factor in the human cholera pandemic remains unclear, this toxin belongs to a much larger class of pore-forming toxins (PFTs) secreted by a wide variety of human pathogens (5).…”
mentioning
confidence: 99%